Review on Main Drive Torsional Vibration and Roller Coupling Vibration of Rolling Mill - Fan, Xiao B.; Zhao, Bin; Jiang, Yu; Fan, Bing Xu (Recent Patents on Engineering, 2021)
Background: Rolling mill vibration has become one of the most widespread and unsolved problems in the rolling industry, which is called
Keywords: Rolling mill